Performance Evaluation of Batam City Government: A Public Sector Accounting Approach - Khadijah, Khadijah; Ferdila, Ferdila; Maizar, Maizar; Syafitri, Allyah (Jurnal Ilmiah Accusi, 2025)
This study aims to evaluate the organizational performance of the Batam City Government through a public sector accounting approach. In the era of bureaucratic reform and the implementation of an accrual-based accounting system, the evaluation of public organizational performance has become essential to ensure accountability and transparency in regional financial management. The study employs a descriptive-qualitative approach with data collection techniques including documentation review, interviews, and an analysis of local government financial reports. The findings indicate that the implementation of public sector accounting has contributed to improving budget management efficiency, program implementation effectiveness, and the quality of financial reporting. However, several challenges remain, including limitations in human resource competencies and the suboptimal use of information technology. This study recommends strengthening the capacity of government personnel and enhancing performance measurement systems based on public sector accounting data as strategic steps to improve good governance within the Batam City Government.